DEVELOPMENT OF A FUNCTIONAL FOOD: MILK CHOCOLATE FORTIFIED WITH ANTHOCYANIN FROM BROKEN RICEBERRY - Ngamdee, Paradorn; Bunnasart, Apisara; Sonda, Atitaya (Life Sciences and Environment Journal, 2019)
The consumption of functional foods, healthier foods, could reduce the risk of non-communication diseases, the major cause of the casualty of the Thai population. Broken Riceberry, an underutilized agricultural byproduct, is rich in anthocyanins, the antioxidants that prevent the diseases. In this study, the anthocyanin-rich extract from broken Riceberry was used as a functional ingredient to produce healthier milk chocolate products. The milk chocolates were prepared by replacing the cocoa powder with the anthocyanin powder (anthocyanin was encapsulated in maltodextrin) by 0 (MC0), 21 (MC21), 42 (MC42) and 70 % w/w (MC70). The total anthocyanin content in the MC21, MC42 and MC70 chocolates increased sequentially (11.1, 83.2 and 107.1 mg cyanidin-3-glucoside equivalent/100 g) with the anthocyanin powder content while it was not detected in MC0. Consequently, the DPPH antioxidant activity of MC0, MC21, MC42, and MC70 respectively increased from 70.7, 72.1, 74.3 to 76.4 %. Maltodextrin, the major constituent in the anthocyanin powder, caused the decrease of the chocolate hardness from 16.6 N (MC0) to the lowest of 9.6 N (MC70). The MC42 received the highest sensory scores (7.0-7.7) for the color, flavor, taste, texture, and overall acceptance attributes. These results indicated that anthocyanin extracted from broken Riceberry could be used as a health benefit functional ingredient for producing healthier foods.